Judgment (Trial) in Absentia According to the Code of Criminal Procedure of the Republic of Albania - Tota, Naim; Skenderaj , Klodjan (Richtmann Publishing, 2021)
The judgment in absentia of the defendant is included in the institutes provided in the Code of Criminal Procedure, where in many cases many problems have been encountered in our case law. The judgment in absentia must, on the one hand, guarantee the respect of the fundamental rights of the defendant and, on the other hand, guarantee the public interest in the administration of justice, through the regular exercise of judicial functions. In the Albanian legislation these conflicts of interest have been resolved by the legislator by accepting and becoming part of the Code of Criminal Procedure of 1995 as well as with the amendaments made in 2017, namely, the conduct of the trial in the absence of the defendant. However, this Code also guarantees the defendant the opportunity to review the matter, in cases where he becomes aware of the decision rendered in absentia. The guarantee placed by the legislator in the code of criminal procedure has come precisely because of the practice of the ECHR but also a series of decisions of the Constitutional Court of Albania, which stated that in cases of judgments rendered in absentia, defendants have the right to have their case reviewed. This paper will analyze exactly the provisions of the Albanian criminal procedural law on the conduct of the judgment in absentia, the cases of suspension of the trial for the defendants who do not know effectively about the trial.Â Â Received: 20 April 2021 / Accepted: 29 May 2021 / Published: 8 July 2021